Analisis Evaluasi Dampak Pembangunan Jembatan Ring Road Terhadap Sosial Ekonomi Masyarakat Nelayan Di Kampung Tobati Kota Jayapura - Marthen Luther Sowe; Yundy Hafizrianda; Elisabeth Lenny Marit (Universitas Cenderawasih, 2014)
The author conducted research on the evaluation of the impact of development on the ring road bridge socioeconomic Tobati fishing village located in the district of South Jayapura Jayapura. The purpose of this study the authors analyzed the impact arising from the construction of the bridge on the ring road Tobati fishing village that in view of the positive and negative impacts in terms of socioeconomic fishing community, using the Analytic Hierarchy Process method of analysis that is in short AHP approach B/C Ratio. By using these tools create a hierarchy in which the author has a purpose for bringing in a major priority of the ring road bridge construction by comparing the positive impact of the economic criteria of social and economic negative social impacts. By using informants from each group are experts in their field value, the authors obtained data is needed to prove the analysis conducted focusing on the ring road bridge construction. Thus the results of the main priorities in the can from the results of the comparison matrix in AHP, the main priority of the ring road bridge construction impact on the social negive berkuranya seen on marine life. Keywords : Evaluation of bridge construction ring road